2019
DOI: 10.1007/s11816-018-00513-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the chloroplast genome-based InDel markers in Niitaka (Pyrus pyrifolia) and its application

Abstract: Pears (Pyrus spp.) are one of the most important fruit crops in temperate regions and are self-incompatible. Large numbers of interspecific hybrids occur naturally and, have been artificially produced in breeding programs. Also, many pear cultivars were generated from intraspecific crossing. Some varieties have been cultivated for a long time, but their breeding history remains unknown. The P. pyrifolia cv. Niitaka is one of key varieties in the Korean pear breeding program. Therefore, its complete chloroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In particular, DNA barcodes are widely used to identify herbal medicines [92][93][94]. In addition, because information on the cp genome can be easily recognized with the development of NGS technology, many studies have reported the development of markers using genetic variations such as indels and SNPs through genome comparison [95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DNA barcodes are widely used to identify herbal medicines [92][93][94]. In addition, because information on the cp genome can be easily recognized with the development of NGS technology, many studies have reported the development of markers using genetic variations such as indels and SNPs through genome comparison [95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…ionanthus subspecies is expected. Interestingly, some studies such as Pyrus cultivars [38] report a relatively high variability among low taxonomic ranks.…”
Section: Analysis Of Genome Featuresmentioning
confidence: 99%
“…For the mutations of sequences, the single nucleotide polymorphism (SNP) and deletion or insertion (InDels) of nucleotide bases are the most common variations in the sequences of plastome (Decesare, Hodkinson & Barth, 2010;Kim et al, 2015). These variations have provided ideal information for developing polymorphic markers for numerous applications such as molecular barcoding (Okoth et al, 2016;Zong et al, 2019), phylogenetic reconstruction (Peterson, Romaschenko & Johnson, 2010), biogeographic studies (Kress et al, 2009;Xie et al, 2019), assessment of the maternal line of hybrid species (Schroeder, Höltken & Fladung, 2011;Tomar et al, 2014;Chung et al, 2019), and clarification of the evolutionary relationship between cultivated and crop wild relatives (Gao et al, 2019). Currently, with the advancement of next-generation sequencing technologies (NGS), sequencing of chloroplast genomes and the development of plastid genetic markers have become feasible in various plant genetic researches (Brozynska, Furtado & Henry, 2014;Bi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%